(untitled) (International Journal of Food and Nutritional Sciences, 2022)
A study has been made to assess the noise pollution at thirty different locations in yoga city Rishikesh, which is lies between Latitude 30° 06’ 12.12" N and 27°29′N and Longitude 78° 17’ 41.11" E. During each sampling of noise, 25readings of SPL were recorded at an interval of 30 seconds in a period of 10 minutes from 5 January 2021 to 30 January 2021 for the parameters such as L10, L50, L90, Lmax, and Lmin in addition to Leq in different categorized vicinity. The results revealed that minimum and maximum pollution of noise levels varied between 56.1 to 83.6 dB (A) Leq. in the city. Based on the questionnaire survey, 70% of respondents reported headache, 90% sleeplessness, 48% hypertension, 75% stress, 80% irritation, and Before and after the lockdown period, respectively, (60%) and (82%) of respondents reported feeling no disturbance due to noise. Higher Noise level produces direct and cumulative inauspicious effects on the health of existing population and animal and it also humiliate suburban, societal and working environment with consequent real and insubstantial losses. The noisy environment also rises as one of the crucial poisons of circumstance. From researches noise pollution is a globally major problem including India. Noise level in the study area is found higher than the standard limits prescribed by CPCB. The present assessment will be key for the awareness of the public and authorities to take any action to control noise pollution and protect society from its unfavorable effects.